UPAYA MENINGKATKAN MOTIVASI DAN PRESTASI BELAJAR PESERTA DIDIK MUATAN PELAJARAN PPKN MELALUI MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA E-EDUMAGZ DI KELAS III SD NEGERI CIMANGGU 01 - Shabrina, Salsa; Nugroho, Agung (Universitas Muhammadiyah Bangka Belitung, 2024)
This classroom action research is motivated by students' low motivation and academic achievement in Civics Education learning in Grade III of SD NEGERI CIMANGGU 01 (Cimanggu 01 Public Elementary School). This research aims to solve students' low motivation and academic achievement through the application of PBL strategies assisted by E-Edumagz (Electronic Educational Magazine) media in Civics Education learning in Grade III of Cimanggu 01 Elementary School. This research was conducted in two cycles, each consisting of two meetings. The research subjects were 24 students in Grade III. The data were collected using observation sheets, evaluation sheets, questionnaires, and documentation. The results of this study show a gradual increase in student motivation and academic achievement. In the first cycle, academic achievement yielded an average score of 76.5 with a completion rate of 64.58% (rated as fair), which subsequently improved in the second cycle to an average score of 84.5, accompanied by a completion rate of 85.4% (rated as good). Similarly, in the first cycle, learning motivation reached a completion rate of 74.24% (rated as fair), and this increased in the second cycle to a completion rate of 80.86% (rated as good). The use of PBL strategies assisted by E-Edumagz (Electronic Educational Magazine) media has positively impacted student motivation and academic achievement in accordance with the expected success indicators.